Narrative Anacrusis: A Descriptive Analysis in Healthy Adults Speaking English - Rangarathnam, Balaji; Bhaskaran, Sreejyothi; Manjula, R (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Anacrusis is the tendency to produce one or more unstressed syllables at the beginning of an utterance in a language. Such syllables are often pronounced rapidly and strongly reduced in duration. Anacrusis has been reported extensively in music, while studies related to spoken language are sparse. This study aimed to analyze the occurrences of anacrusis in narrative speech of healthy Asian-Indian adults speaking English. This was carried out by perceptually identifying the intonation groups and to identify anacrustic and non-anacrustic occurrences with reference to the primary stress and to acoustically verify the presence of ‘anacrusis using the measure verage syllable duration index. Ten healthy Asian-Indian adults [5 males and 5 females] within the age range of 18-25 years, proficient in English, participated in the study. The task was to narrate on a topic (college life) for 1 minute. The samples were audio recorded and perceptually analyzed for primary stress. Further, the average syllable duration of each utterance was calculated. Results suggest that anacrusis was often noticed in the initial part of the intonation groups but there were few instances where the anacrustic segments occurred in the medial or final positions also. More identifications of primary stress were observed in the non-anacrustic utterances compared to the anacrustic utterances. Average syllable duration increased as the word position moved from first word position to the final word position in an intonation group suggesting the presence of anacrusis. The anacrustic and non-anacrustic segments in each intonation groups on an average exhibited a 1/3rd: 2/3rd representation.